Fuelling a food nation - Kang, Soon Chen (2012)
RICE shortage hit an all time high during the global food crisis in 2008 when the price of Thai white rice soared to US$l,000(RM 3,100) per tonne compared to US$360 (RM 1, 119 ) the year before, triggering panic in Asian nations where rice is the most important staple food.